Enteral Ca-Intake May Be Low and Affects Serum-PTH-Levels in Pre-school Children With Chronic Kidney Disease - Lilith Schmitz; Pamela Hoermann; Birgit Trutnau; Augustina Jankauskiene; Ariane Zaloszyc; Alberto Carlo Edefonti; Claus Peter Schmitt; Guenter Klaus; Guenter Klaus (Frontiers Media S.A., 2021)
Treatment of chronic kidney disease (CKD) mineral bone disorder (MBD) is challenging in growing children due to the high amount of calcium needed for normal bone mineralization and the required dietary phosphate restriction, which often includes intake of calcium-rich products such as milk. Therefore, enteral calcium-intake (Ca-I) was calculated.Patients: We looked at pediatric CKD-Patients aged 0-6 years.Design: We used a retrospective analysis of Ca-I from dietary data collections. Ca-I below 60% or above 100% of the D-A-CH and the KDOQI reference values were considered as severe Ca deficiency or Ca overload, respectively.Results: We had 41 children, median age 1.1 (range 0-5.8) years, body weight 7.3 (2.4-19.9) kg, and length 68 (48-105) cm at the time of first dietary data collection. Renal function was classified as CKD stage III in 20, IV in 28, V in 44, and VD in 142 dietary data collections. At the first dietary data collection, 5 children were in the CKD stage III, 10 in IV, 9 in V, and 17 were on dialysis. Only one child progressed to a higher CKD stage. In total, 234 dietary data collections were analyzed, and 65 follow-up collections were available from 33 children after a time interval of 26 (1-372) days. The median caloric intake was 120 (47-217)% of D-A-CH RDI. In 149 (63.6%) of the dietary data collections, enteral Ca-I was below the target (<100% of the D-A-CH and KDOQI RDI). Severe Ca-deficiency was found in 11 (26%) and 4 (12%) of the children at the first and second dietary data collection, respectively. In total, 11 children were on Ca-containing phosphate binders. In dietary data collection 1 and 2, there were seven children. From these, 4/7 and 4/7 patients had an enteral total Ca-I above the 100% D-A-CH-limit or above the KDOQI limit, respectively. Absolute dietary Ca-I and Ca-I normalized to body weight correlated negatively with PTH (r = −0.196, p < 0.005 and r = −0.13, p < 0.05).Conclusion: Enteral Ca-I should repeatedly be monitored in CKD children because many may may otherwise be underexposed to enteral calcium and overexposed when calcium-containing phosphate binders are given. Our findings suggest a major impact of dietary calcium supply on bone health in pediatric CKD.